A statistical study of some social and economic aspects of the family in seven selected towns in the south-western Cape region - Pansegrouw, Nicolaas Jacobus de Wet (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.Soc.) -- University of Stellenbosch, 1948.